Integrating Virtual Reality Into English Language Instruction: Assessing Efficacy And Student Motivation - Nafisatul Lutfi; Andhina Ika Sunardi; Agnes Nora Eko Wahyu Utami; Rofiatun Nafiah (Mathematics Education Study Program, 2025)
This study investigates the effectiveness of incorporating Virtual Reality Videos into the English language learning model at Universitas Teknologi Digital Indonesia. Employing a quasi-experimental design, the researcher implemented two distinct learning methods across separate class groups. One group utilized the Virtual Reality learning model, while the other adhered to traditional instructional methods. The assessment of the learning model's efficacy employed statistical tests and questionnaire analyses administered to participants post-learning sessions, coupled with classroom observations. Results from the research revealed that students utilizing Virtual Reality videos achieved higher scores compared to those using conventional videos. While questionnaire responses indicated relatively comparable outcomes, Virtual Reality videos demonstrated a marginal advantage concerning student learning experiences and motivation. This study contributes valuable insights into the pedagogical benefits of integrating VR technology, emphasizing its positive impact on language acquisition within the higher education context